Implementasi Pembelajaran Kitab Kuning Dengan Arab Pegon di Pondok Pesantren Roudhotut Tholibin Ulya Susukan Kabupaten Semarang: Muhammad Ikhsanuddin*, Isa Anshory, Ngatmin Abbas - Muhammad Ikhsanuddin; Isa Anshory; Abbas, Ngatmin (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
The education of Kitab Kuning and Arab Pegon bears significant relevance in the cultural and Islamic educational context in Indonesia. This research explores the implementation and challenges of learning Kitab Kuning with Arab Pegon at the Roudhotut Tholibin Ulya Islamic Boarding School in Susukan Semarang. A qualitative method is employed, involving participatory observation, in-depth interviews, and content analysis. It is found that the learning of Kitab Kuning with Arab Pegon creates direct engagement between teachers and students, enriching theoretical understanding with practical application. The integration of instrumental and shari'a knowledge with contemporary needs prepares students to apply religious teachings in the context of modern life. The research results indicate that this method has a positive impact on shaping students' readiness to face the moral and ethical challenges of this era.